247PRole of ADC values in assessing response after chemoradiotherapy in cervix cancer and in identifying residual disease. (24th November 2019) - Koyyala, V P B; Jajodia, A; Chaturvedi, A K; Mahawar, V; Sharma, M; Goyal, P; Talwar, V; Goyal, S; Doval, D C
Abstract: Background: Evaluate Role of ADC values in assessing response to chemoradiotherapy in cervix cancer & contribution of contrast MRI to identify residual disease, post-treatment completion. Methods: Prospective observational study in 100 patients of histopathologically proven cancer of the uterine cervix. Based on clinical outcome integrating final histopathological diagnosis patients were classified as either complete response or Residual disease. Validity & reliability of PET-CT, Contrast MRI, and ADC values were checked by calculating sensitivity, specificity, PPV & NPV. Results: Residual lesions have significantly lower ADC value than that of post-treatment changes. Mean ADC values of residual tumors: 1.26±0.238 x 10-3 mm2/s and mean ADC values of lesions due to post-treatment changes: 1.540 ±0.218 x 10-3 mm2/s (statistically significant difference in between malignant and post-treatment lesions p < 0.05). ADC sensitivity 67%, specificity 83%, PPV 35%, NPV 95 % and accuracy 81% in differentiating residual disease from post-treatment changes. PPV, NPV, sensitivity, and specificity with PET-CT was 93%, 89%, 98%, and 73%. PPV, NPV, sensitivity, and specificity of contrast MRI was 16%, 91%, 58%, and 59%. Conclusions: Diffusion imaging differentiates residual cervix malignancies from post-treatment changes based on ADC values and can be a promising and evocative biomarker. Complimentary use of ADC and PET/CT may increase diagnostic confidence. However, the cost and logistics of MRI imaging is an important factor in routine clinical implementation especially in developing countries like India, where carcinoma cervix is associated with poor socioeconomic status. Legal entity responsible for the study: Rajiv Gandhi cancer Institute and Research Centre, New Delhi. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.